Proposing instrument to measure impression management among flood victims - Salleh, Nurul ‘Aaina; Mustaffa, Che Su; Mohd Taib, Ariffin (International Association of Computer Science and Information Technology Press (IACSIT Press), 2013)
Abstract—Flood disaster is one of the events that have an impact on the lives of the individuals involved in Malaysia.Destruction and loss make a person feels depressed besides being worried.Even worse when the victims become depressed as a result of the incident. Flood events can be seen as a threat to the well-being of individuals both physically and emotionally.This article will discuss how stress, anxiety and depression are relatedtothe quality of life and well-being of flood victims.The discussion is based on the Stressful Life EventsTheory, Freud’s Anxiety Theory, Beck's Cognitive Theory of Depression and the Quality of Life Conceptual Model.